Mine Sealants - Their Uses & Benefits - M. E. Herrera (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
The use and effectiveness of sealants in under-ground mines is a recognized and well accepted practice by many people in the mining industry. Their use however in many cases is to correct, or attempt to correct, problems that might have been avoided with sealant use in the early stages of development, and continued thereafter.